Survey of pediatric MDCT radiation dose from university hospitals in Thailand: A preliminary for national dose survey - Supika Kritsaneepaiboon (2018)
Background: Increasing pediatric CT usage worldwide needs the optimization of CT protocol examination. Although there are previous published dose reference level (DRL) values, the local DRLs should be established to guide for clinical practice and monitor the CT radiation. Purpose: To determine the multidetector CT (MDCT) radiation dose in children in three university hospitals in Thailand in four age groups using the CT dose index (CTDI) and dose length product (DLP). Material and Methods: A retrospective review of CT dosimetry in pediatric patients (,15 years of age) who had undergone head, chest, and abdominal MDCT in three major university hospitals in Thailand was performed. Volume CTDI (CTDIvol) and DLP were recorded, categorized into four age groups: ,1 year, 1-,5 years, 5-<10 years, and 10-<15 years in each scanner. Range, mean, and third quartile values were compared with the national reference dose levels for CT in pediatric patients from the UK and Switzerland according to International Commission on Radiological Protection (ICRP) recommendation. Results: Per age group, the third quartile values for brain, chest, and abdominal CTs were, respectively, in terms of CTDIvol: 25, 30, 40, and 45 mGy; 4.5, 5.7, 10, and 15.6 mGy; 8.5, 9, 14, and 17 mGy; and in terms of DLP: 400, 570, 610, and 800 mGy cm; 80, 140, 305, and 470 mGy cm; and 190, 275, 560,765 mGy cm. Conclusion: This preliminary national dose survey for pediatric CT in Thailand found that the majority of CTDIvol and DLP values in brain, chest, and abdominal CTs were still below the diagnostic reference levels (DRLs) from the UK and Switzerland regarding to ICRP recommendation.